2005
DOI: 10.1038/sj.jea.7500461
|View full text |Cite
|
Sign up to set email alerts
|

The Washington aerial spray drift study: Children's exposure to methamidophos in an agricultural community following fixed-wing aircraft applications

Abstract: This study characterized exposures of eight children living in an agricultural community near potato fields that were treated by aerial application with the organophosphorus (OP) insecticide, methamidophos (O,S-dimethyl phosphoramidothioate). Exposure monitoring included air and deposition samples in the outdoor community environment, outdoor and indoor air samples at each residence, wipe samples of playground equipment, toys, indoor surfaces, and children's hands, and periodic urine samples. Monitoring occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 20 publications
0
42
0
1
Order By: Relevance
“…Aerial application was the most frequent application method found in drift events, accounting for 249 events (39%). Drift hazards from aerial applications have been well documented (CDC 2008; Weppner et al 2006). Applicators should use all available drift management measures and equipment to reduce drift exposure, including new validated drift reduction technologies as they become available.…”
Section: Discussionmentioning
confidence: 99%
“…Aerial application was the most frequent application method found in drift events, accounting for 249 events (39%). Drift hazards from aerial applications have been well documented (CDC 2008; Weppner et al 2006). Applicators should use all available drift management measures and equipment to reduce drift exposure, including new validated drift reduction technologies as they become available.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research in North Carolina showed that farmworkers had little knowledge of the pesticides used where they work, and that they did not have information about pesticides applied to dwellings that were rented or grower-provided (Arcury et al 2001; Early et al 2006). Drift has been shown to result in the dispersal of agricultural pesticides to dwellings on surrounding land (Fenske et al 2000b; Ward et al 2006; Weppner et al 2006). Finally, agricultural communities have generally higher levels of environmental pesticides compared with nonagricultural communities, with residues from discontinued pesticides found in contemporary rural environments and homes (Lu et al 2004; Quandt et al 2004; Wolz et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that, in agricultural communities, residues in house dust and yard soil of the most common category of agricultural pesticides, organophosphates, are inversely associated with distance from treated fields (Simcox et al, 1995; Loewenherz et al, 1997; Lu et al, 2000). Lu et al (2000) found that children living near treated orchards had statistically significantly higher levels of pesticide metabolites in their urine as compared to children living more distant, and Weppner et al (2006) confirmed pesticide residues on playground equipment, toys and childrens’ hands after aerial spraying of surrounding potato, corn and wheat fields. In a study of adult NHL, homes within 750 meters of crop fields had concentrations of agricultural herbicides more than 4-fold higher than those with no crops (Ward et al, 2000).…”
Section: Discussionmentioning
confidence: 85%